ANALISIS NASKAH DRAMA “BAPAK” KARYA BAMBANG SOELARTO MENGGUNAKAN PENDEKATAN OBJEKTIF - Anggraini, Suhesti; Devi, Wika Soviana (Jurnal Komposisi, 2022)
Drama is a performing art where actors portray a story on stage for an audience. This research analyzes the drama "Bapak" by Bambang Soelarto, which tells the story of a father who loves his children and his country. The purpose of this descriptive study is to provide an accurate description of the facts, characteristics, and relationships between the phenomena being investigated. The drama is set in Yogyakarta in 1949 and follows a linear plot with four main characters: Bapak, Si Sulung, Si Bungsu, and Perwira. An objective approach is used to analyze the theme, plot, setting, characterization, and message in the drama. The theme of the "Bapak" drama is patriotism and the struggle for national independence. The message is that as a nation that loves our country, we must defend the independence of our homeland from the hands of the colonizers, even if it means sacrificing everything